Bakım Çalışanlarına Hastalardan veya Danışanlardan Gelen Cinsel Taciz Davranışları Ölçeği Türkçe Geçerlilik Güvenilirlik Çalışması: Metodolojik Araştırma. - AYAR, Duygu; ÇAKI, Burcu; AKSU, Çiğdem (Turkiye Klinikleri Journal of Nursing Sciences, 2022)
Objective: The study aimed to perform the Turkish reliability and validity analysis of the "Sexual Harassment Behaviors from Patients or Clients and the Care Workers' Mental Health". Material and Methods: The sample of the methodological study consisted of 167 nurses. In the study data were collected digitally. In the study, the size of samples was determined to be at least 10 times the number of items in the scale in order to perform factor analysis. The translation-re-translation method was used for the language validity of the scale. Validity studies in the study were carried out with exploratory and confirmatory factor analysis. Reliability studies of the scale were calculated with internal consistency coefficients. Before data collection, nurses participating in the study were informed about the study and their online consent was obtained. Ethics committee approval was obtained to conduct the study. Results: As a result of the analysis, it was determined that the scale consisted of 12 items and 3 sub-dimensions as Observed Sexual Harassment, Verbal Sexual Harassment, and Physical Sexual Harassment, in line with the original structure of the scale. The item loads of the scale ranged from 0.555 to 0.862, and the fit index values were calculated as Ki-kare Testi (X2/sd)=2.18, Goodness of Fit Index=0.90, root mean square error of approximation=0.08, Comperative Fit Index=0.90, root mean square residuals=0.02, Adjusted Goodness of Fit Index=0.84. The Cronbach alpha internal consistency coefficient for the whole scale was found to be 0.843. Cronbach alpha internal consistency coefficients for nonverbal sexual harassment, verbal sexual harassment and physical sexual harassment sub-dimensions were found to be 0.761, 0.768 and 0.807, respectively. Conclusion: The analyzes showed that the scale is a valid and reliable measurement tool with robust psychometric properties that can measure sexual harassment behaviors towards care workers.